PENGARUH SUPERVISI PENDIDIKAN KEPALA SEKOLAH TERHADAP MUTU PENDIDIKAN DI MTS MADANI ALAUDDIN KABUPATEN GOWA - Suarga; Fina (Department of Islamic Education Management, 2023)
The purpose of this study was to find out (1) An overview of the educational supervision of principals at MTs Madani Alauddin, Gowa Regency, (2) An overview of the quality of education at MTs Madani Alauddin, Gowa Regency and (3) The significant influence of educational supervision on the quality of education at MTs Madani Alauddin Regency Gowa. The type of this research is quantitative research. The population in this study is 541 people consisting of 47 educators and education staff and 494 students, then a sample of 123 people is taken which is a combination of 40 educators and education staff and 83 people learners. The sampling technique used is saturated sampling and proportional stratified random sampling. The instrument used in this research is a questionnaire and documentation. The results of this study indicate that 1) Educational supervision is in the medium category with a percentage of 60%, 2) The quality of education is in the medium category with a total percentage of 62.5%. The quality of education (students) is in the medium category with a percentage of 66%, and 3) Obtained tcount 3.391 > ttable 1.686, which means that there is a significant influence between the education supervision of the principal on the quality of education at MTs Madani Alauddin, Gowa Regency.